STRATEGI PENGUATAN KOMPETENSI SDM TEKNOLOGI INFORMASI&KOMUNIKASI (TIK) DALAM MENGOPTIMALKAN PENERAPAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) - Ludi Awaludin . (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Governance based on the development of information technology and innovation requires human resources who have competence in the application of Electronic Based Government Systems (SPBE), namely the administration of government that utilizes information and communication technology to provide services to SPBE Users. Strategy Improvement of human resource (HR) competence in Information & Communication Technology (ICT) at the Department of Communication and Information and Statistics of West Bandung Regency is done through e-learning methods on computer network competence, programming competence and Multimedia competence. Implementation through the learning of e-learning methods, especially with the introduction of Electronic-Based Government System (SPBE), obtained an average of 9.09 results, which shows that the introduction of SPBE has succeeded in increasing the competence of HR in Information & Communication Technology (ICT) at the Office of Communication and Information Technology and Statistics of West Bandung Regency.